Antimicrobial sensitivity profile of bacteria isolated from milk of cows with mastitis in family farms (Research, Society and Development, 2020)
The objective of this study was to investigate the etiology and sensitivity profile of Gram positive bacteria isolated from the milk of cows with mastitis. Milk samples were analyzed from the Nova Jerusalem, community located in the municipality of Paragominas, Southeast Region of the state of Pará. Of the total of 24 samples collected, 24.56% of the isolates were identified as Staphylococcus aureus, 14.03% as coagulase-negative Staphylococcus and 3.51% Streptococcus spp. The Staphylococcus aureus showed sensitivity to ceftiofur, enrofloxacin, streptomycin, neomycin, and norfloxacin, and higher resistance to bacitracin, penicillin G, and sulfonamides, the samples of coagulase-negative Staphylococcus were shown to be sensitive to the antimicrobials cephalothin, ceftiofur, enrofloxacin, streptomycin, and norfloxacin, and showed greater resistance to bacitracin and lincomycin, whereas in the samples that were isolated Streptococcus spp., were observed higher percentages of sensitivity against cephalothin, ceftiofur, gentamicin, and norfloxacin, and higher resistance to bacitracin and penicillin G. The results obtained may be related to the fact that the antimicrobials that showed bigger efficiency are not routinely used in the treatment of the animals studied, mainly because they have a higher market value, in relation to those that obtained greater microbial resistance.